Psychiatric symptoms and mental health court engagement. Issue 6 (2nd July 2016) - Canada, Kelli E.; Markway, Greg; Albright, David
ABSTRACT: People with mental illnesses are overrepresented in the criminal justice system. Many interventions have been implemented to treat the underlying causes of criminal justice involvement and prevent people with mental illnesses from recidivating. Mental health courts (MHC) are one of these programs. This analysis examines the relationship between psychiatric symptoms and MHC engagement. Eighty MHC participants from two Midwestern MHCs were interviewed. Symptom severity was assessed at baseline using the Brief Psychiatric Rating Scale. MHC engagement was estimated by treatment adherence, substance use, days spent in jail, probation violations, and MHC retention during a six-month follow-up period. Using nonparametric statistical tests and logistic regression, results indicate symptoms of depression, anxiety, and guilt are more severe at baseline for those people who are incarcerated during the follow-up period. Symptoms of anxiety are more severe for people who are terminated or went missing during the follow-up period. Further research is needed to determine the directionality and causality of these relationships. MHCs professionals should be aware of the relationship between symptom severity and MHC engagement and attempt to connect participants with treatment and services as early as possible and individualize treatment plans based on current symptoms and need.